Letter : Scottish Ambulance Unit - Elger, William
041-0112-001 SCOTTISH TRADES UNION CONGRESS GENERAL COUNCIL. WILLIAM ELGER. J.P SECRETARY. PHONE CENTRAL 3179 33 ELMBANK CRESCENT. GLASGOW, November 6th. 1936. Personal. Sir Walter M. Citrine, Transport House, Smith Square, London, S.W.1. Dear Sir Walter, Scottish Ambulance Unit Many thanks for yours of the 4th inst., the contents of which I have noted. Yours truly Wm Elger 292/946/41/112